Research and deployment on the innovation solution for 4G voice of high-speed railway scenario - DePing XU; XiangChen MA; RiTao CHENG; LuJing GENG (Dianxin kexue)
High-speed railway is a special scenario of 4G network coverage,the project planning and construction of high-speed railway 4G network coverage have special difficulty,wireless coverage is different.High-speed railway scenario 4G voice solution needs to use different voice deployment strategy according to the quality of wireless coverage.The current situation of high-speed 4G network planning index and the ability to support voice services were analyzed,the alternative voice program under the high-speed railway 4G coverage was researched.Considering enhancing the user experience and feasibility,the feasible high-speed railway scene 4G voice service deployment recommendations was put forward.